Enhancement of sensory attributes and mineral content of Sourdough bread by means of microbial culture and yeast (Saccharomyces Cerevisiae). (October 2022) - Zahra, Anam; Farooq, Umar; Saeed, Muhammad Tariq; Quddoos, Muhammad Yousaf; Hameed, Amna; Iftikhar, Madiha; Noreen, Amna; Zahra, Syeda Mahvish; Hussain, Ashiq; Bukhari, Syeda Ramsha; Rafique, Ayesha; Naqvi, Syeda Nimra; et al.
Abstract: Background: Bread is one of the basic food stuffs which have been eaten all over the planet. In recent years, consumers have selected various alternatives of white bread due to high glycemic index and low fiber content. Objective: This study prepares the sourdough bread with microbial strains for improving sensory attributes and enhancing availability of minerals. Materials and methods: Three Lactic acid bacterial strains L. Plantarum Е90, L. Brevis Е12, and L. acidophillus ATCC4356 and specific doses of yeast Saccharomyces Cerevisiae were used to prepare sourdough bread. The standard solutions of minerals were run for analysis by flame atomic absorption spectrophotometer (Model: AA-6300, Kayoto, Japan). The sourdough was evaluated for pH and minerals and sensory evaluated by different panels of expert judges using nine-point hedonic scales. Results: The results showed that overall sensory characteristics (crust color, acid flavor, acid taste, texture, chewability and acceptability) were obtained significant in culture dose of 2%, culture type C2 ( L. Brevis Е120 ) and fermentation time of 6 h. Fermentation and optimum acidity (lower pH) was obtained in C2 ( L. Brevis Е120 ) and C3 L acidophilus ATCC4356. The mineral bioavailability (Fe and Zn), significant results were obtained from culture type C3 ( L. acidophillus ATCC4356 ), culture dose of 1.5% and 2% and fermentation time of 6 h. Conclusion: The sourdough bread prepares by using culture type C2 ( L. Brevis Е120 ), improves sensory qualities and C3( L. acidophillus ATCC4356 ) improves nutritional level in sour dough bread. Graphical abstract: Image, graphical abstract